Measuring social variables in real and artificial faces. (November 2018) - Balas, Benjamin; Tupa, Lauren; Pacella, Jonathan
Abstract: Human observers rapidly make social judgments about faces, including estimates of trustworthiness, aggression, and many other personality states and traits. Are social variables like these estimated effectively from artificial faces? If not, this could easily compromise interactions between humans and social agents. We examined how a set of personality variables were estimated from real face images and artificial face images synthesized from the original photographs using a morphable model of facial appearance. This stimulus set provided us with an identity-matched set of real and artificial agents, allowing for a close comparison of how social variables are estimated as a function of animacy. We found that observers' ratings of social variables in both cases were well-described using a two-factor model of social "face space" based on valence and dominance, but real vs. artificial scores were only correlated along the valence axis. Further, we found that correlations between real and synthetic face social variables depended critically on sex categories, suggesting that social evaluation in artificial agents depends on male/female appearance. Highlights: We compared social face space for real and synthetic faces. Real and synthetic faces yielded similar dimensional models. Individual faces were positioned differently within each model.